Understanding Fracture Risks in Pakistan’s Aging Population: A Meta-Analysis of Risk Factors and Population Variability: Fracture Risks in Aging - Khan, Sher Dil; Haider, Usman; Kanwal, Romina; Aslam, Syeda Saba (Pakistan Journal of Health Sciences, 2025)
With the demographic shift of Pakistan towards ageing population, fractures are increasing in this cohort at an alarming rate. Pakistani elderly are bearing some unique risk factors due to some specific environmental, socio-demographic, cultural and genetic susceptibilities. Objective: To explore risk factors specific for Pakistani elderly so that appropriate prevention strategies can be adapted by the officials. Methods: A comprehensive meta-analysis and systemic review was conducted across all studies done in Pakistan. Newcastle-Ottawa Scale (NOS) scored the quality of studies, while Funnel plots and Egger’s regression tests were used to assess publication bias. Random effect model was used for statistical analysis. Results: A substantial combined effect, despite the variability among the studies, was noted. The exclusion of lower-quality studies had minimal impact on the overall effect size (OR = 1.25, 95% CI: 1.10–1.40) and heterogeneity (I² = 35% vs. I² = 37%), indicating robust findings across varying study quality. Funnel plot was relatively symmetric, indicating no substantial publication bias and consistency. The limited number of studies and narrow distribution indicated a homogeneous set of results with minimal variability. Conclusions: Risk factors identified included Vitamin D deficiency leading to increased incidence of osteoporosis. Alzheimer’s disease was found to be a much neglected but growing concern for increased fracture risk in this population. Pakistani women are at increased risk due to low bone mineral density, shorter hip axis length, cultural practices.